MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA MATA PELAJARAN AKIDAH AKHLAK DALAM MEMBENTUK KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK DI MAN 2 MOJOKERTO - Sutrisno; Ainur Rofiq (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model in the subject of Akidah Akhlak in developing students’ critical thinking skills at MAN 2 Mojokerto and to identify its supporting and inhibiting factors. This research employed a qualitative descriptive approach. Data were collected through non-participant observation, interviews, and documentation. The data analysis process included data collection, data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the implementation of PBL enhances students’ learning activities in analyzing problems related to Akidah Akhlak material, fosters critical thinking skills, and encourages active collaboration and group discussion. Students demonstrated high enthusiasm and active participation during the learning process. Supporting factors include teacher readiness, the use of varied instructional strategies, and school environment support, while inhibiting factors consist of time limitations and differences in students’ abilities in understanding the given problems.